Strategies to Increase Marketplace Customer Loyalty - Tri Lestari (Jurnal Administrasi Bisnis, 2022)
In recent years, the marketplace has become a favorite as a trusted distribution channel to get sales profits and loyal customers, especially during the COVID-19 pandemic in Indonesia in March 2020, where people prefer to make purchases online. Everyone needs both primary needs and secondary needs. The study was conducted using quantitative methods with multiple linear regression, F test, coefficient determination, normality test, heteroskedasticity test, and multicollinearity test. The tests were based on questionnaires distributed using Google forms to 168 respondents consisting of 72 percent of women and 28 percent of men, to see how much influence predictive variables used had on increasing customer loyalty. Customer loyalty to the marketplace depends not only on the services provided by the marketplace provider but also on the product or service provider. The combination of predictive variables from marketplace providers and product or service providers in the form of prices, shipping costs, logistics, and payment systems in this study significantly influenced customer loyalty output variables. A determination coefficient of 51.62 percent also provides evidence that the predictive variables used in this study effectively increase customer loyalty variables.